Ability of Moringa Ore (Moringa Oleifera) As Biosorbent in Used Cooking Oil Processing - Buluk, Susana; Leto, Kristina Tresia; Nisa, Kartini Rahman (Lembaga Riset Mutiara Akbar, 2023)
The results of this study stated that the use of activated moringa ore biosorbents had a great influence on the quality of cooking oil both physically and chemically. The results of data analysis based on variations in contact time and dose variations can show that free fatty acid levels have decreased but are not in accordance with the stipulated SNI, namely 0.17%. Activation of Moringa ore using Sodium Hydroxide (NaOH) can reduce the levels of free fatty acids in used cooking oil. Variation of biosorbent contact time can affect the decrease in fatty acid levels, which occurs at the optimum contact time of 90 minutes, the free fatty acid percentage of 0.17% is not in accordance with SNI. Variations in biosorbent doses can also affect the increase in free fatty acid levels, namely the optimum dose of 1.00-gram percentage of free fatty acids decreased by 0.17% not according to SNI. Variations in contact time and variations in optimum doses of biosorbents can also affect color organoleptic tests and the smell of used cooking oil. Where the results of each respondent's statement that 95% of the refined oil using Moringa ore biosorbent are similar to new cooking oil, namely with a bright yellow color. The method used in this study is a quantitative method by conducting experiments on the subjects to be studied and used as a reference for finding and obtaining data directly through observation or experimentation